2020
DOI: 10.1007/s00404-020-05472-y
|View full text |Cite|
|
Sign up to set email alerts
|

Localization of claudin-2 and claudin-3 in eutopic and ectopic endometrium is highly similar

Abstract: Purpose Claudins as the major components of tight junctions are important in maintaining cell–cell integrity and thus function as a barrier. Dysregulation of the claudins is often associated with loss of the epithelial phenotype, a process called epithelial–mesenchymal transition (EMT), which most often results in gain of migrative and invasive properties. However, the role of claudins in the endometrium or endometriosis has only rarely been examined. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Up to now, only four studies were published regarding claudin expression in endometriosis with their findings summarized in Table 3 . In contrast to one study showing cycle-dependent differences of mRNA expression of claudins [ 80 ], three studies found no differences in expression of claudins-2–4 and 11 [ 83 , 84 , 85 , 86 ]. Again, no significant differences between the eutopic endometrium of women with and without endometriosis could be shown for claudins-2–4, 7, and 11 ( Table 3 ).…”
Section: The Role Of Emt In Endometriosismentioning
confidence: 71%
See 4 more Smart Citations
“…Up to now, only four studies were published regarding claudin expression in endometriosis with their findings summarized in Table 3 . In contrast to one study showing cycle-dependent differences of mRNA expression of claudins [ 80 ], three studies found no differences in expression of claudins-2–4 and 11 [ 83 , 84 , 85 , 86 ]. Again, no significant differences between the eutopic endometrium of women with and without endometriosis could be shown for claudins-2–4, 7, and 11 ( Table 3 ).…”
Section: The Role Of Emt In Endometriosismentioning
confidence: 71%
“…Furthermore, the co-expression of epithelial and mesenchymal markers in the same cell or in a subset of cells remains to be clarified. In the case of a partial EMT in endometriosis, we observed a strong expression of cell–cell contacts in nearly all endometrial and endometriotic glands, as well as in nearly all epithelial cells [ 85 , 86 , 88 ], thus suggesting that the partial EMT might occur in the same cell(s).…”
Section: Emt In Endometriosis—when Does It Happen?mentioning
confidence: 88%
See 3 more Smart Citations